An Electron/Ion Dual‐Conductive Alloy Framework for High‐Rate and High‐Capacity Solid‐State Lithium‐Metal Batteries. Issue 3 (21st November 2018) - Yang, Chunpeng; Xie, Hua; Ping, Weiwei; Fu, Kun; Liu, Boyang; Rao, Jiancun; Dai, Jiaqi; Wang, Chengwei; Pastel, Glenn; Hu, Liangbing
Abstract: The solid‐state Li battery is a promising energy‐storage system that is both safe and features a high energy density. A main obstacle to its application is the poor interface contact between the solid electrodes and the ceramic electrolyte. Surface treatment methods have been proposed to improve the interface of the ceramic electrolytes, but they are generally limited to low‐capacity or short‐term cycling. Herein, an electron/ion dual‐conductive solid framework is proposed by partially dealloying the Li–Mg alloy anode on a garnet‐type solid‐state electrolyte. The Li–Mg alloy framework serves as a solid electron/ion dual‐conductive Li host during cell cycling, in which the Li metal can cycle as a Li‐rich or Li‐deficient alloy anode, free from interface deterioration or volume collapse. Thus, the capacity, current density, and cycle life of the solid Li anode are improved. The cycle capability of this solid anode is demonstrated by cycling for 500 h at 1 mA cm −2, followed by another 500 h at 2 mA cm −2 without short‐circuiting, realizing a record high cumulative capacity of 750 mA h cm −2 for garnet‐type all‐solid‐state Li batteries. This alloy framework with electron/ion dual‐conductive pathways creates the possibility to realize high‐energy solid‐state Li batteries with extended lifespans. Abstract : An electron and Li‐ion dual‐conductive framework is built on a garnet‐type solid‐state electrolyte for solid Li‐metal batteries. The dual‐conductive framework facilitates electron and ion transfer in the solid Li‐metal anode during cycling and realizes high‐rate and high‐capacity Li anodes in solid‐state batteries.